Slavic Philosophy in the Philosophical Thought of the Slovak Romantics - with Polish Traces in the Background: pl - Goszczyńska, Joanna (Poznańskie Studia Slawistyczne, 2023)
The author of the article focuses on introducing and interpreting the dispute over Slavic philosophy that took place in the 1840s in Slovak magazines (between J.M. Hurban, C. Zoch and P.Kellner-Hostinský). This dispute is an important testimony of the era, it concerned the fundamental issues of the time: the identity of Slovak culture, its philosophical background, its place and role in the Slavic world, its attitude to tradition. The author of the article focused primarily on two aspects of the “slovanská veda” project: the relation to German philosophy and the key cognitive category “viďeňja.” The author also points to the role that this dispute played in shaping the model of Slovak culture. Since the Slovak Romantic literary discourse has recently been enriched by many new revisions, the author also briefly refers, sometimes polemically, to the latest research.